The nucleolin MoNsr1 plays pleiotropic roles in the pathogenicity and stress adaptation in the rice blast fungus Magnaporthe oryzae - Zhang, Zhen; Islam, Mohammad Shafiqul; Xia, Jiuzhi; Feng, Xiangyang; Noman, Muhammad; Wang, Jing; Hao, Zhongna; Qiu, Haiping; Chai, Rongyao; Cai, Yingying; Wang, Yanli; Wang, Jiaoyu (Frontiers in Plant Science, 2024)
The rice blast disease, caused by the fungus Magnaporthe oryzae, is a significant agricultural problem that adversely impacts rice production and food security.Understanding the precise molecular pathways involved in the interaction between the pathogen and its host is crucial for developing effective disease management strategies. This study examines the crucial function of the nucleolin MoNsr1 in regulating M. oryzae physiological functions. ΔMoNsr1 deletion mutants showed reduced fungal growth, asexual sporulation, and pathogenicity compared to the wildtype. Mutants exhibited impaired conidial germination and appressoria formation, reducing infection progression. Additionally, ΔMoNsr1 deletion mutant had less turgor pressure, confirming that MoNsr1 is essential for cell wall biogenesis and resistant to external stresses. Furthermore, ΔMoNsr1 deletion mutant showed enhanced sensitivity to oxidative stress, reactive oxygen species, and cold tolerance.Our results offer a thorough understanding of the function of MoNsr1 in the virulence and stress-resilient capability in M. oryzae. These findings provide insights into the novel targets and contribute to the emergence of innovative approaches for managing rice blast disease.